A splice site variant in TCTN3 underlies an atypical form of orofaciodigital syndrome IV. (30th August 2022) - Hussain, Shabir; Nawaz, Shoaib; Khan, Hammal; Acharya, Anushree; Schrauwen, Isabelle; Ahmad, Wasim; Leal, Suzanne M.
Abstract: Orofaciodigital syndrome (OFD) is clinically heterogeneous and is characterized by abnormalities in the oral cavity, facial features, digits, and central nervous system. At least 18 subtypes of the condition have been described in the literature. OFD is caused by variants in several genes with overlapping phenotypes. We studied a consanguineous Pakistani family with two affected siblings with an atypical form of OFD type 4 (OFD4). In addition to the typical features of OFD4 that include limb defects and growth retardation, the siblings displayed rare features of scaphocephaly and seizures. Exome sequencing analysis revealed a novel homozygous splice site variant c.257‐1G>A in TCTN3 that segregated with disease. This homozygous splice site variant in TCTN3 is most likely the underlying cause of the atypical form of OFD4 observed in this family. Our results contribute to the phenotypic spectrum of TCTN3 associated ciliopathies and will facilitate better clinical diagnosis.